Alat Keamanan Pintu Menggunakan E-KTP, Modul RFID dan AWS EC2 berbasis NODEMCU ESP8266 - Verdian Ramdhani; Rahmat Hidayat; Hendrick (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
The current door locking sistem still uses conventional keys, making it less efficient for homes with many doors because there are too many keys to carry. In addition, conventional locks are easily opened by thieves and also locks can be duplicated by irresponsible people. So that a more practical and efficient lock is needed, from this problem the author has the idea to produce a safe and practical RFID-based door security device. By utilizing E-KTP as an RFID tag as a security for the door of the house. Design and build a house door security using the NodeMCU ESP8266 microcontroller as a circuit controller. This study uses the Research and Development method, which is a method that aims to produce or develop certain products. Based on the test results, it can be concluded that the simulation of the door safety device can operate properly, according to the design made. The RFID reader used has a frequency of 13.56 Mhz which is placed on the door to read the E-KTP ID and sent to the AWS server with AWS EC2 as the website infrastructure to add other information and be stored in the MySQL database. If the ID is not in the database, Led The red light will light up and the buzzer will sound. If the ID is in the database, the servo motor will pull the door latch The yellow LED will light up, and will close the door again within 10 seconds.